Water quality hydrology on surface mined watersheds - Rowe, Jerry W., author; Longenbaugh, Robert A., advisor; McWhorter, David B., committee member; Sunada, Daniel K., committee member (Colorado State University. Libraries, 1976)
Water quality and discharge on four watersheds disturbed by surface coal mining at the Edna Mine in northwestern Colorado have been monito red for about three years. Water quality and discharge have also been monitored in an adjacent stream at points above and below the entrance of mine drainage into the stream. Dissolved solids inflow to the stream between these two points equaled 6.lx106 kg in 1974 and 5.3x106 kg in 1975 for an increase in dissolved solids load of two to three times along the reach of the stream adjacent to the mine. About 70 to 80 percent of the dissolved solids inflow occurs in April, May, and June. During spring runoff dissolved solids reach concentrations exceeding 700 mg/ℓ at the downstream monitoring site with corresponding concentrations of less than 150 mg/ℓ at the upstream site. Dissolved solids concentrations in combined runoff on the four mine watersheds ranged from annual averages of 1200 mg/ℓ to 3000 mg/ℓ. The pre-mining concentration of dissolved solids in combined runoff is estimated at 460 mg/ℓ with the higher concentrations on the mine watersheds attributable to the disturbance caused by mining. Mining increases the depth of water percolation from several meters or less on undisturbed land to about 20 meters on mined land. Data show that the disturbed geologic material in the spoils contains large quantities of soluble salts. A single-equation model based upon water and mass balances has been developed which can predict the average annual TDS concentration of combined surface and subsurface runoff from a mined watershed. The model incorporates three hydrologic parameters, three chemical parameters, and the fraction of land disturbed by mining. Concentrations predicted using the model on the Edna Mine watersheds had an average error of about 9 percent from the measured concentrations. Parameters in the model can be adjusted to simulate the effects of varied climatic and hydrologic conditions that may result from reclamation efforts. The model may prove to be a useful tool for the planning and management of water resources on surface mine lands.
Keywords: Strip mining -- Environmental aspects; Mine drainage; Groundwater -- Pollution